B cell depletion therapy for 19 patients with refractory systemic lupus erythematosus. Issue 5 (26th November 2007) - Podolskaya, A; Stadermann, M; Pilkington, C; Marks, S D; Tullus, K
Abstract : Objective: B cell dysregulation is involved in the development of childhood-onset systemic lupus erythematosus (SLE). The safety and efficacy of B cell depletion therapy is evaluated in the the largest series of children to be presented in the literature. Methods: 19 children (89% female) with SLE, aged 6–16 (median 14) years, treated with rituximab in a single centre were retrospectively reviewed. The British Isles Lupus Assessment Group (BILAG) index and biochemical, haematological and immunological parameters were evaluated before and after treatment, with the primary outcome assessed as normal results. Rituximab therapy was used for acute life- or organ-threatening symptoms or symptoms that had not responded to standard treatment. The range of symptoms included lupus nephritis, cerebral lupus and severe general symptoms. Rituximab 750 mg/m 2 was given intravenously twice, usually within a 2-week period. Patients were followed up for 6–38 (median 20) months. Results: Rapid reduction of SLE disease activity was observed within the first month, represented by a reduction of BILAG scores (14 to 6, p<0.005) and an improvement in renal function (estimated glomerular filtration rate of 54 to 68 ml/min/1.73 m 2, p = 0.07), immunological (complement C3: 0.46 to 0.83 g/l, p = 0.02) and haematological (haemoglobin: 9.7 to 10.3 g/dl, p = 0.04) parameters. No serious side effects were observed, except for herpes zoster in five cases. Conclusion: In our cohort of children, rituximab was safe and effective when used in combination with standard immunosuppressive agents. Randomised controlled studies are needed to further evaluate the safety and efficacy of rituximab therapy.